2023
DOI: 10.3390/d15020256
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis before Enzymes: Thiol-Rich Peptides as Molecular Diversity Providers on the Early Earth

Abstract: The multiplicity of simple molecules available on the primitive Earth probably made possible the development of extremely diverse prebiotic chemistry. The importance of thiols is widely recognized in the community studying the origin of life. De Duve’s “thioester world” has been considered a major contribution in this regard, where thioester bonds have high energies and thus can contribute to several chemical reactions. Herein, we propose specific models of thiols that exhibit unique activities toward several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…What we have tried to prove here is that starting from relatively simple molecules, complex mixtures can be obtained [25]. Thus, from the aminothiol-containing amidonitrile 11 (Cys-Met-CN) or 12 (Cys-Ala-CN), an array of compounds is observed after a few hours.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…What we have tried to prove here is that starting from relatively simple molecules, complex mixtures can be obtained [25]. Thus, from the aminothiol-containing amidonitrile 11 (Cys-Met-CN) or 12 (Cys-Ala-CN), an array of compounds is observed after a few hours.…”
Section: Discussionmentioning
confidence: 94%
“…What we have tried to prove here is that starting from relatively simple molecules, complex mixtures can be obtained [25]. Thus, from the aminothiol-containing amidonitrile Some examples of the found linear polypeptides that contain thiazoline rings are shown in Table 3.…”
Section: Discussionmentioning
confidence: 96%
“…These acylations have been identified by their presence in many proteins, such as histones and mitochondrial proteins, which may alter their biological activity [189,[191][192][193]. It has also been suggested that these modifications may contribute to the aging process and have contributed to the development of simple metabolic pathways in primordial life [194][195][196][197][198][199][200]. Table 12 provides the calculated reaction thermodynamic values for the model reactions of these mentioned reactions, with compound 54 serving as a model for succinyl-CoA, yielding the acylated product 55 with methylamine serving as the lysine side chain; compound 56 serving as a model for glutaryl-CoA, yielding product 57; compound 58 serving as a surrogate of 3-hydroxy-3-methylglutaryl-CoA and producing 59; and compound 60 serving as a model for 3-methylglutaryl-CoA and yielding the N-acylated product 61.…”
Section: Click Reactionsmentioning
confidence: 99%